Traditional Meat Products of the North Eastern Region of India: Scope and Opportunities - Laskar , Saurabh Kumar (Current Perspectives in Agriculture and Food Science Vol. 6, 2023)
The chapter explores the significance and diversity of traditional meat products across various regions in Northeast India. It highlights the cultural, social, and ecological aspects of preparing and consuming these traditional dishes. The article acknowledges the threat posed by modern lifestyles to these culinary traditions and emphasizes the need for systematic study and preservation. The study comprehensively overviews traditional meat products from different states, such as Arunachal Pradesh, Sikkim, Meghalaya, Nagaland, Mizoram, Manipur, and Tripura. Each state's unique offerings are described, including the ingredients used, preparation methods, and cultural significance. However, the article identifies certain limitations and health concerns associated with traditional food practices, such as using smoked and fermented products that might contribute to carcinogenic compounds or health risks. The article also highlights the potential for commercializing these traditional dishes, which could contribute to regional economies and job creation. In conclusion, this chapter emphasizes the importance of preserving and documenting traditional meat products as a vital aspect of cultural heritage. It also identifies the need to address health concerns and adapt traditional practices to changing dietary habits while maintaining their cultural value.